Cepat baca BM / Shazwan Sharif Abd Shukur - Shazwan, Sharif Abd Shukur (2004)
Computer based aided learning that has been introduced since 1950's are believed to be highly potential to become a teaching tool. Now, the CAL learning tools can be achieved as CD ROMs, web based system and a lot more. This increasing is due to the rapidly grown of home computer among people. However, here in Malaysia, this new ways of learning are new to the citizens and a lot of teaching methods still using books as a teaching tool. Cepat Baca BM project has been conducted from 15th June 2003 until 12th February 2004. This project tries to develop a teaching method aiding the children learning to read Malay Language by using CAL concepts. This thesis consist of 8 chapters from Introduction; that briefly explain on the "Cepat Baca B M' system, Literature Review; that shows the finding from other teaching systems and techniques, Methodology; to describe the methodology to be use in developing the system, System Analysis; explain the system needs, the users needs, and the tools and software that are needed to develop this system, System Architecture; that presented the complete system design explanations, System Implementation; explaining the phase involve between design phases to the implementation, Testing; show the test that have been conducted to the developed system and lastly the, Conclusion; the overall conclusion about the system that has been developed can be found in this chapter.